Relationship between chip colour and compositional characters in potato (Solanum tuberosum) - KUMAR, RAJ; MARWAHA, R S; GOPAL, J; PANDEY, S K (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2004-07 to evaluate 52, 72 and 72 germplasm accessions for relative importance of 5 compositional factors, namely, reducing sugars, dry matter sucrose, phenols and amino acids of tubers to chip colour. Correlation, path analysis and multiple regression studies showed that reducing sugars and dry matter were important constituents in determining the chip colour in freshly harvested potatoes. The correlation of reducing sugar content with chip colour was positive and significant. Tuber dry matter had a significant and negative correlation with the intensity of chip colour. Dry matter had a negative and significant correlation co-efficient with reducing sugars. The low reducing sugar and high tuber dry matter contents had both direct and indirect favourable effects on chip colour. As the low reducing sugars and high dry matter were associated with each other and both contributed to lighter chip colour, simultaneous selection for both of these parameters will better facilitate the development of potato varieties suitable for chipping. The multiple regression based on both these characters explained more variation in chip colour compared to either of these characters. Between the two, reducing sugar was more important and both reducing sugars and dry matter explained